Mechanism of Gegen Qinlian Decoction in the treatment of diabetic cataract based on network pharmacology and experimental validation - Juanjuan Xia; Xin Wang; Xiaomei Fu; Weihong Zhong; Wenting Wu; Liping Yu; Ruixiang Xu; Jing Tang; Ting Gui; Jing Liu; Shuhong Peng; Weifeng Zhu (Tissue and Cell, 2027)

Particle-associated distribution, sedimentary accumulation, and SSD-based ecological risk assessment of organochlorine pesticides in the East China Sea - Jie Fu; Longkun Sun; Yan Zhang; Wenqing Wang; Zhongyu Cui; Zhen He; Chun-Ying Liu; Dong-Liang Lu; Gui-Peng Yang (Marine Environmental Research, 2026)

The ferric Iron uptake transcriptional regulator (Fur) governs virulence and stress responses in Listeria monocytogenes and serves as a target for novel food safety interventions - Aiyun Li; Haonan Xu; Ruofei Song; Ge Song; Arshad Qandeel; Qiyu Cao; Xiaohui Zhang; Tongxin Ge; Wenxin Wang; Yiyang Li; He Sun; Jinxuan Gui; et al. (Food Research International, 2026)

Study on the size effect model of mode I fracture characteristics in Longmaxi formation shale based on DIC and acoustic emission technology - Yu Suo; Xian-hang Wei; Gui-quan Wang; Cui-long Kong; Guang-chao Zhang; Xi Chen; Xiaofei Fu; Zhe-jun Pan; Bin Huang (Soil Dynamics and Earthquake Engineering, 2026)

Flash Joule heating as a novel thermal treatment for heavy metal detoxification from municipal solid waste incineration fly ash - Zili Yang; Qiongyu Yang; Yanzhen Fu; Yangchao Xia; Yuhao Chang; Shiqi Dai; Haoqiang Cheng; Xiahui Gui (Journal of Environmental Chemical Engineering, 2026)

Polysiloxane-enabled dual-interphase engineering coupled with fluorescence diagnosis of Ni2+ dissolution for 4.6 V lithium metal batteries - Hankun Zhang; Jiacheng Yan; Benhua Wang; Jinqiang Gao; Chao Fu; Rui Zhang; Xiaowei Huang; Xiaowei Tang; Zhengzhao Yang; Kefei Wang; Bowei Ju; Xiangzhi Song; et al. (Chemical Engineering Journal, 2026)

Microscopic deformation mechanism of clay aggregates in view of the montmorillonite particles rearrangements under cyclic loading-unloading conditions - Zi-Yu Ding; Kai-Wen Tong; Yong-Gui Chen; Qiong Wang; Wen-Jie Dai; Xing-Guang Zhao; Chang-Fu Wei; Zhi-Jun Zhang (Applied Clay Science, 2026)

Legacy-to-Alternative Shift of Brominated Flame Retardants in the East China Sea Revealed by Multimedia Observations and Coupled Modeling - Jie Fu; Xing Liu; Gu Tao; Haibo Zhang; Ye Kong; Zhen He; Chun-Ying Liu; Dong-Liang Lu; Gui-Peng Yang (Water Research, 2026)

Digital infrastructure construction and urban green transition: A quasi-natural experiment based on the broadband China policy using double machine learning - Tiangui Lv; Xianzhe Huang; Menghan Yuan; Gui Jin; Qiao Zhao; Shufei Fu (Sustainable Cities and Society, 2026)

Genesis of boltwoodite in the hinterland surface of the Taklamakan Desert: Implication for exploration of sandstone-hosted uranium deposits - Liqun Wu; Shouyu Wang; Yangquan Jiao; Gui Wang; Liang Yue; Zhenpeng Tao; Wenlong Yang; Rui Chu; Mingzheng Zhang; Yingli Fu; Bingqian Li (Journal of Geochemical Exploration, 2026)

Constraint or promotion? Revealing linkages between environmental regulation and green technology diffusion in the Yangtze River Delta Urban Agglomeration - Tiangui Lv; Qiao Zhao; Gui Jin; Shufei Fu; Anying Chen (Environment, Development and Sustainability, 2026)

Protein-based hydrogels for food safety and human health - Gui Fu; Jie Hou; Qian Wu; Rongrong Xiong; Pradeep K. Malakar; Yongheng Zhu; Yong Zhao; Zhaohuan Zhang (Critical Reviews in Food Science and Nutrition, 2026)

Exploring the therapeutic mechanism of kaempferol in acute lung injury: Network pharmacology and experimental validation - Zhu-ying Zhou; Chen-xi Zhang; Xiu-ling Wei; Chuan-fu Wu; Da-gui Chen; Fu-sheng Shang; Chun-ming Jiang (Tissue and Cell, 2026)

Activating valence oscillations in reconstructed high-entropy selenide for self-stabilized seawater oxidation through localized lattice oxygen redox - Hai Li; Xiaoliang Zhang; Yangyang Liu; Taiping Fang; Xue Zou; Gui Wang; Shun Wan; Hongliang Dong; Zihao Lu; Yufan Wu; Jinhui Fu; Luobin Cao; et al. (Science Bulletin, 2026)

Variations in semi- and non-volatile organic substances during physical recycling and their migration from rPET bottles - Yi-Qi Liu; Yan Zeng; Shao-Fu Zeng; Zhi-Wei Wang; Lei Zhu; Li-Li Jin; Gui-Qin Shang; Gui-Hua Liu; Chang-Ying Hu (Food Packaging and Shelf Life, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

Radiative cooling coatings and natural ventilation in urban street canyons: Synergies and trade-offs - Cheng-Peng Ma; Yu-Fei Tang; Shang-Xian Zhao; Gui-Xiong Yang; Fu-Yun Zhao; Yuguo Li; Rongpeng Zhang (Building and Environment, 2026)

Structurally diverse monoterpenoid indole alkaloids from Damnacanthus hainanensis as well as their potential anti-inflammatory and anti-HIV effects - Gui-Qiong Wu; Long-Cheng Cui; Ye-Ping Liu; Chen-Xu Yue; Lin-Xuan Li; Tian-Yu Wang; Yu-Shan Wang; Shu-Ri Li; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2026)

Microsphazaphilones H–Y: new azaphilone pigments with HIV latency reversal activity from the marine-derived fungus Microsphaeropsis arundinis P1B - Qing-Ren Lu; Xian-Yuan Yang; Lei Li; Lei-Ming Wu; Lu-Xiang Wan; Yi-Fan Fu; Xian-An Chen; Xin-Xiang Xu; Tao Yuan; Xin Chen; Abrar Ahmed; Nirmal Malik; et al. (Marine Life Science & Technology, 2026)

Synthesis of rhodamine modified carbon quantum dots and application of ratiometric fluorescence detection for Cu2+ and triple-mode detection for 2,4-dichlorophenoxyacetic acid - Qing Li; Yage Guan; Qian Wang; Daxiang Gui; Yingqiang Fu (Analytica Chimica Acta, 2026)

Numerical investigations of flow fields around polyethylene terephthalate (PET) nets using Improved Delayed Detached Eddy Simulation - Gang Wang; Zhi Wang; Chang-tao Guan; Zhao-qi Jiao; Jia-jun Hu; Lian-hui Wu; Xiao-yu Qu; Fu-kun Gui; De-jun Feng (Ocean Engineering, 2026)

Study on progressive collapse resistance of steel beam-column structures with column tree connection under edge column failure - Jian-Gui Qin; Sheng-Yu Lu; Wei-Wei Zhang; Feng Fu; Kai Qian (Engineering Structures, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

MdERF106 modulates malate accumulation in apple fruit by activating MdALMT9 - Xu Xu; Lin Zhao; Renzhi Gui; Weihong Fu; Sanhong Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Maritime aerial object detection via dual-domain contrastive learning and low-light degradation enhancement - Liwen Liu; Jiayi Xu; Gui Fu; Xiaoqiang Zhang; You Wang; Rong Fan (Frontiers in Marine Science, 2026)
The expansion of marine economic activities and the increasing demand for maritime security have positioned drone-based aerial object detection as a crucial technology for applications such as marine environmental monitoring and maritime law enforcement. However, maritime aerial imagery remains highly challenging due extreme illumination variations, the small size and indistinct appearance of targets. This paper introduces a novel dual-domain contrastive learning framework integrated with low-light degradation enhancement to address these challenges. First, a low-light degradation perception module performs illumination equalization, improving image uniformity under adverse lighting conditions. Then, a dual-domain contrastive learning strategy aligns representations across both image and feature domains, enabling the detection network to learn more discriminative features. Additionally, a Local Feature Embedding and Global Feature Extraction Module (LEGM) is incorporated into the detection network to enhance the representation of small-scale maritime targets. Experiments on SeaDronessee and AFO datasets demonstrate the superiority of the proposed approach, achieving an improvement of 4.3% in mAP@0.5 and 1.9% in mAP@0.5:0.95 on SeaDronesSee, 1.9% in mAP@0.5 and 1.1% in mAP@0.5:0.95 on AFO. These results confirm that the proposed method delivers robust and accurate maritime object detection under complex environmental conditions and has strong potential for deployment in real-world maritime surveillance applications.

3D-printed fish-scale dam-like structured photothermal evaporators based on thiol-ene click chemistry for solar-driven freshwater production and salt recovery - Lixuan Yang; Xiaoyu Fu; Zhihan Xu; Feiyue Zhou; Jingxing Gui; Yuting Xue; Yuxuan Ma; Dan Yu; Wei Wang (Journal of Cleaner Production, 2026)

Genistein-7-O-octanoate: a promising natural antioxidant for stabilizing soybean oil during storage and high-temperature frying - Gui Fu; Yuanyuan Yan; Yongfu Li; Zhaohuan Zhang; Mingfu Wang; Yueliang Zhao (Food Research International, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Spatial distribution, source, and ecological risk of organochlorine pesticides (OCPs) in the Yellow and Bohai Seas - Long-Kun Sun; Jie Fu; Ming-Liang Zhao; Wen-Qing Wang; Zhen He; Gui-Peng Yang (Marine Environmental Research, 2026)

Occurrence, fate, and integrated risk profiling of legacy and novel brominated flame retardants in the Yellow and Bohai Seas - Jie Fu; Xing Liu; Mingliang Zhao; Longkun Sun; Huian Jin; Wenqing Wang; Helin Sun; Dong-Liang Lu; Gui-Peng Yang (Journal of Hazardous Materials, 2026)

Enhanced flotation upgrading of high-ash fine waste coal with a novel compound collector: High-value and clean utilization of waste - Zili Yang; Yuhao Chang; Yanzhen Fu; Qieyuan Gao; Guoxiao Wang; Yangchao Xia; Yaowen Xing; Xiahui Gui (Journal of Cleaner Production, 2026)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Integrated process of flocculation-UF- membrane absorption for the treatment of rare earth refining wastewater and recovery of NH4Cl - Yiwen Wang; Qinliang Jiang; Jianxin Li; Zhenyu Cui; Li Wu; Shuanglin Gui; Jiaqi Fu (Journal of Environmental Chemical Engineering, 2025)

Alternating copolymer-based flame-retardant gel polymer electrolyte for high-safety lithium metal batteries - Chao Fu; Huafeng Cao; Hankun Zhang; Yueping Wang; Zhenhuan Zhang; Jianxiu Wang; Gui-Chao Kuang; Benhua Wang; Xiangzhi Song; Libao Chen (Chemical Engineering Journal, 2025)

Characterisation of cytochrome c oxidase-coding genes from mung bean and their response to cadmium stress based on genome-wide identification and transcriptome analysis - Yan Leng; Zhuan-Bin Niu; Shao-Hua Liu; Fu-Jun Qiao; Gui-Fang Liu; Bin Cheng; Shi-Weng Li (Molecular Biology Reports, 2025)

Transcriptomic profiling reveals mechanism, therapeutic potential, and prognostic value of cancer stemness characteristic in nasopharyngeal carcinoma - Jin-Wei Chen; Run-Nan Shen; Jiang-Quan Zhu; Ying-Hang Wang; Liang-Min Fu; Yu-Hang Chen; Jia-Zheng Cao; Jin-Huan Wei; Jun-Hang Luo; Jia-Ying Li; Cheng-Peng Gui (Functional & Integrative Genomics, 2025)

A comparative study of RNN, CNN, LSTM and GRU for random sea wave forecasting - Xin Jin; Chao Dai; Yuan Tao; Fu-gui Zhang (Ocean Engineering, 2025)

Accelerating light-driven bioreaction with interfacial engineered microalgae-bacteria consortia: Unraveling positive charge-mediated biological interaction - Haixing Chang; Xueqing Gui; Meina Han; Jingwei Fu; Liandong Zhu; Shih-Hsin Ho (Chemical Engineering Journal, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Stepwise recovery of gallium (Ga), lithium (Li), and rare earth elements (REEs) from roasted coal gangue based on leaching kinetics differentiation - Jingzheng Wang; Hongxiang Xu; Yijun Cao; Kejia Ning; Biao Fu; Lin Ma; Xin Sun; Yuntao Kang; Mengting Hong; Guixia Fan; Xiahui Gui; Jiushuai Deng (Hydrometallurgy, 2025)

What Controls the Distribution of Ore Veins in Quartz Vein-Type Tungsten Deposits: Constrains from Fan-Shaped Mineralization in SE China - Gui-Cong Fang; Deng-Hong Wang; Fu-Qiang Yang; Zhan-Xu Ni; Chang-Shuai Huang; Ping Wang; Meng Feng; Zuo-Hai Feng (Journal of Earth Science, 2025)

Role of macrophage ATP metabolism disorder in SiO2‑induced pulmonary fibrosis: a review - Hui-jie Hu; Yuan-yuan Fu; Shu-ling Du; Yu-han Zhang; Zhao-qiang Zhang; Gui-zhi Han (Purinergic Signalling, 2025)

IRBITs, signaling molecules of great functional diversity - Ying Liu; Xuhui Feng; Han Wu; Tianxiang Gui; Mingfeng Fu; Xudong Luo; Lei Zhao; Li-Ming Chen (Pflügers Archiv - European Journal of Physiology, 2025)

Research on the value assessment methods for natural resource damage on typical uninhabited islands: A case study of an uninhabited island subject to tourism development - Hai-Yan Wu; Shi-Feng Fu; Xiao-Qiong Cai; Yi-Biao Wu; Feng-Gui Chen; Zhi-Xiao Song; Jian Wu; Xiang Pan (Journal of Environmental Management, 2025)

A systematic review on mechanism and regulation strategy of marine hydrodynamic noise: Advances, challenges, and perspectives - Xin Jin; Hua-long Huang; Yuan Tao; Fu-gui Zhang; Min Luo; Chang-yuan Fan; Tao Tang (Ocean Engineering, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

The effect of catalyst preparation methods on biomass hydrothermal liquefaction: Exploring cleaner and more efficient pathways for catalytic hydrothermal liquefaction of biomass - Gui-zhong Deng; Xiao-dong Tang; Jing-jing Li; Si-hao Ling; Fu-xiang Yang; Shun-guo Wang (Fuel, 2025)

Causal relationship analysis and risk assessment of contributing factors in coal mine ordinary accidents: A case study (2002–2023) - Chenhui Yuan; Gui Fu; Jiangshi Zhang; Yongtun Li; Meng Han; Yuxuan Lu; Jinkun Zhao; Zhirong Wu (Process Safety and Environmental Protection, 2025)

Study on the nitrogen migration of different biomass by activated carbon-based MOF catalyst in hydrothermal environment - Gui-zhong Deng; Xiao-dong Tang; Jing-jing Li; Lin-yu Zhang; Zhi Yang; Fu-xiang Yang (Fuel, 2025)

Redox state of NAD modulates the activation of Na-bicarbonate cotransporter NBCe1-B via IRBIT and L-IRBIT - Tianxiang Gui; Ying Liu; Mingfeng Fu; Han Wu; Pan Su; Xuhui Feng; Mengmeng Zheng; Zixuan Huang; Xudong Luo; Walter F. Boron; Li-Ming Chen (Science China Life Sciences, 2025)

Numerical study of deformation inhomogeneity and its effect on mechanical properties of the heavy-wall offshore pipeline fabricated by different processes - Ling-zhi Xu; Gui-ying Qiao; Ying-long Ma; Yu Gu; Kai Xu; Xiao-wei Chen; Fu-ren Xiao (Ocean Engineering, 2025)

Highly efficient and convenient QuEChERS using ZIF-67 derived magnetic nanoporous carbon for determination of carbamate pesticides in various vegetable and fruit samples - Zi-Ling Li; Xiao-Run Qi; Yi-Heng Xu; Jia-Qi Zhao; Gui-Fu Zuo; Man-Man Wang (Food Chemistry, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Erwinia aeris sp. nov., A Novel Bacterium Isolated from the Surface of an Ore in Hubei Province, China - He-Bao Guo; Hong-Tu Zhu; Yi-Fan Zhang; Fu Yang; Xiao-Tong Ma; Shi-Gui Li; Hai-Lei Wei; Xiao-Xia Zhang (Current Microbiology, 2025)

A new diterpenoid alkaloid from the Aconitum scaposum - Cheng-En Fu; Gui-Fang Li; Guo-Qing Sun; Shuai Huang; Lin Chen; Xian-Li Zhou (Phytochemistry Letters, 2025)

The flotation deashing separation performance of high-ash fine coal-slime using humic acid depressant and insights to its depressant mechanism - Zili Yang; Yangchao Xia; Yanzhen Fu; Qinshan Liu; Ming Li; Xiahui Gui (Fuel, 2025)

Innovative coupling pathway for second- and third-generation biomass: Efficient L-lactate synthesis from xylose and C1 compounds - Ya Wu; Gen Lu; Ruiqi Zeng; Zeyang Li; Xin Xu; Yifan Gui; Chonghao Guo; Lizhen Deng; Yutong Bie; Derui Zhang; Yuxin He; Yuyang He; et al. (Chemical Engineering Journal, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

In-situ Stress Characteristics and Tectonic Significance of the Hongnipo Copper Mine in the Sichuan-Yunnan Region - Jun Fu; Yong-gui Chen; Han Zhou; Wen-lian Liu (Geotechnical and Geological Engineering, 2025)

Deciphering flows: Spatial correlation characteristics and factors influencing carbon emission intensity in the Yangtze River Delta - Tiangui Lv; Qiao Zhao; Shufei Fu; Gui Jin; Xinmin Zhang; Han Hu; Guoliang Xu (Journal of Cleaner Production, 2024)

Light driven depolymerization of tobacco waste: A multi-scale simulations - Jia-hao Wang; Xian-jie Zhang; Lin-can Fang; Wen-xian Chen; An-Fu Hu; Gui-lin Zhuang (Journal of Environmental Chemical Engineering, 2024)

Comprehensive analysis of benzothiazoles (BTHs), benzotriazoles (BTRs), and benzotriazole ultraviolet absorbers (BUVs) in the western South China Sea: Spatial distributions, migration tendencies and ecotoxicological relevance - Ming-Liang Zhao; Jie Fu; Xuan Ji; Jing Zhang; Zhen He; Gui-Peng Yang (Water Research, 2024)

Supplementation with Akkermansia muciniphila improved intestinal barrier and immunity in zebrafish (Danio rerio) - Yawei Wang; Zhenyi Huang; Zewei Gui; Boya Yang; Fu You; Guokun Yang; Xindang Zhang; Xulu Chang; Xiaolin Meng (Fish & Shellfish Immunology, 2024)

Green massive mechanical synthesis of highly efficient Zn-Doped Cs3Cu2I5 for LED and X-ray imaging applications - Qi-Hua Yang; Gui-Hua Li; Yu-Chen Ao; Shu-Juan Zhao; Han-Qi Wei; Le Fu; Zhi-Wei Luo; Tian-Liang Zhou; Chu-Jie Wang; Ge-Mei Cai (Chemical Engineering Journal, 2024)

Analysis of excessive NOx emission from tampered heavy-duty vehicles based on real-time data and its impact on air pollution - Yong Li; Huanqin Wang; Mengqi Fu; Jing Wang; Yanyan Yang; Huaqiao Gui (Atmospheric Pollution Research, 2024)

Tick saliva interference with LTβR signaling facilitates the transmission of Lyme disease spirochetes - Lin Jin; Bao-Gui Jiang; Yizhu Yin; Jingya Guo; Jia-Fu Jiang; Xiaopeng Qi; Gary Crispell; Shahid Karim; Wu-Chun Cao; Ren Lai (Toxicon, 2024)

Enhanced adsorption and visible-light photocatalytic degradation of CIP by CdS QDs‐Decorated Mn-doped NH2-UiO-66 - Hongkun Luo; Yu Gui; Yongli Fu; Xiongjian Li (Journal of Environmental Chemical Engineering, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Determination of chloropropanol esters and glycidyl esters in nutritional foods by gas chromatography–tandem mass spectrometry based on acid hydrolysis and solid-phase extraction - Yi Li; Dan Chen; Wusheng Fu; Yan Yang; Huafeng Chen; Lei Ni; Hongjing Chen; Dingguo Jiang; Sophia Zhang; Rongjuan Gui (Food Additives & Contaminants: Part A, 2024)

Saprobic Dothideomycetes from Yunnan, China: introducing a new species, Queenslandipenidiella lingcangensis , and a new host record for Periconia byssoides - Guang-Cong Ren; Er-Fu Yang; Jutamart Monkai; Kandawatte W. T. Chethana; Heng Gui; Antonio Roberto Gomes de Farias (New Zealand Journal of Botany, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Tough and biodegradable C-lignin cross-linked polyvinyl alcohol supramolecular composite films with closed-looping recyclability - Tao Gui; Ling-Ping Xiao; Shuang-Lin Zou; Yue Zhang; Xu Fu; Chang-Hao Liu; Run-Cang Sun (Chemical Engineering Journal, 2024)

The delaying effect of Clausena lansium extract on pear ring rot is related to its antifungal activity and induced disease resistance - Wen-Wu Song; Xiao-Xiang Fu; Duan-Tao Cao; Xiao-Gui Liang; Su-Ling Xiao; Min-Xuan Yuan; Ying-Jin Huang; Qing-Hong Zhou; Hong-Yi Wei; Jun-Wen Wang; Wen-Wen Peng (Postharvest Biology and Technology, 2024)

Enhancing accident cause analysis through text classification and accident causation theory: A case study of coal mine gas explosion accidents - Qingsong Jia; Gui Fu; Xuecai Xie; Yujingyang Xue; Shihan Hu (Process Safety and Environmental Protection, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Systematic identification of wheat spike developmental regulators by integrated multi-omics, transcriptional network, GWAS, and genetic analyses - Xuelei Lin; Yongxin Xu; Dongzhi Wang; Yiman Yang; Xiaoyu Zhang; Xiaomin Bie; Lixuan Gui; Zhongxu Chen; Yiliang Ding; Long Mao; Xueyong Zhang; Fei Lu; et al. (Molecular Plant, 2024)

Accident case data-accident causation model driven safety training method: Targeted safety training empowered by historical accident data in coal industry - Xie Xuecai; Fu Gui; Shen Shifei; Shu Xueming; Li Jing; Huang Lida; Wei Na (Process Safety and Environmental Protection, 2024)

Accident case-driven study on the causal modeling and prevention strategies of coal-mine gas-explosion accidents: A systematic analysis of coal-mine accidents in China - Wang Yuxin; Fu Gui; Lyu Qian; Wu Jingru; Wu Yali; Han Meng; Lu Yuxuan; Xie Xuecai (Resources Policy, 2024)

Self-assembled Fe3O4-NH2 @g-C3N4 composite for magnetic solid-phase extraction of benzophenones in sea water and lake water coupled with LC-MS/MS determination - Man-Man Wang; Zi-Ling Li; Han Wu; Ke-Yan Chen; Fan Guo; Gui-Fu Zuo; Yu He; Xue-Bo Yin (Journal of Hazardous Materials, 2024)

Mechanical-Effect descriptor for oxygen reduction reaction and hydrogen evolution reaction on Single-Atomic Ni-Graphene catalysts - Wei Zhang; Fu-li Sun; Xue-long Zhang; Shuang-te Zhao; Wen-xian Chen; Gui-lin Zhuang (Fuel, 2024)

Buprofezin affects the molting process by regulating nuclear receptors SfHR3 and SfHR4 in Sogatella furcifera - Gui-Yun Long; Ming-Fu Gong; Hong Yang; Xi-Bin Yang; Cao Zhou; Dao-Chao Jin (Pesticide Biochemistry and Physiology, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

The effect of glycerol additive on high value-added chemicals from tobacco waste pyrolysis - Jia-hao Wang; Xian-jie Zhang; Qian Xia; Shui yang Fang; An-fu Hu; Jun Wen; Sheng-jun Zhou; Wen-xian Chen; Gui-lin Zhuang (Journal of Environmental Chemical Engineering, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

New luminescent hydrophilic iridium(III) nanoflower at low potential for electrochemiluminescence immunosensing - Li Song; Guangrong Kuang; Gui Zhang; Jiang Guo; Yingzi Fu (Chemical Engineering Journal, 2023)

Oxidative pretreatment of refractory gold ore using persulfate under ultrasound for efficient leaching of gold by a novel eco-friendly lixiviant: Demonstration of the effect of particle size and economic benefits - Qihao Gui; Likang Fu; Yuting Hu; Haokai Di; Ming Liang; Shixing Wang; Libo Zhang; Enhua Dong (Hydrometallurgy, 2023)

BCE-Net: Reliable building footprints change extraction based on historical map and up-to-date images using contrastive learning - Cheng Liao; Han Hu; Xuekun Yuan; Haifeng Li; Chao Liu; Chunyang Liu; Gui Fu; Yulin Ding; Qing Zhu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

miR ‐124 mediates the expression of ccBax to regulate Cyprinid herpesvirus 2 ( CyHV ‐2)‐induced apoptosis and viral replication - Yan Fu; Junzhe Zhang; Wenjie Cheng; Xingyu Cheng; Liqun Lu; Lang Gui; Yousheng Jiang; Ye Zhang; Dan Xu (Journal of Fish Diseases, 2023)
Cyprinid herpesvirus 2 (CyHV‐2), the etiological agent of herpesvirus haematopoietic necrosis (HVHN) in carp and goldfish, has caused significant economic losses in the aquaculture industry. During viral infection, the host initiates a series of active or passive defences to regulate the process of virus infection. Apoptosis is a key component of active cellular defence, and members of the Bcl‐2 family have been shown to play a critical role in the apoptotic process. However, the mechanism of action of the Bcl‐2 family in inducing apoptosis during CyHV‐2 infection remains unclear. In this study, we revealed the molecular mechanism of miRNA‐mediated silver crucian carp BAX (ccBax) in CyHV‐2‐induced apoptosis for the first time and demonstrated that the overexpression of miR‐124 suppressed ccBax expression and significantly down‐regulated apoptosis in caudal fin cells of Carassius auratus gibelio (GiCF), while miR‐124 inhibitors were the opposite. These studies indicated that miR‐124 inhibits CyHV‐2‐induced apoptosis by reducing the expression of ccBax. Furthermore, the fact that transfection of miR‐124 mimics promoted CyHV‐2 replication, whereas miR‐124 inhibitors inhibited CyHV‐2 replication, indicated that miR‐124 inhibited CyHV‐2‐induced apoptosis and contributed to viral replication. All these results suggested that miR‐124 suppresses virus‐induced apoptosis and promotes viral replication by targeting and regulating ccBax expression.

Rational design of one inorganic-organic hybrid Z-scheme heterojunction for high-performance photocatalytic water splitting - Cun-biao Lin; Fu-li Sun; Jun Wen; Wen-xian Chen; Gui-lin Zhuang (Fuel, 2023)

Anaerobic co-digestion of thermo-alkaline pretreated microalgae and sewage sludge: Methane potential and microbial community - Jiaqi Fu; Bing Yan; Shuanglin Gui; Yinxuan Fu; Song Xia (Journal of Environmental Sciences, 2023)

Ellagic acid induces apoptosis and autophagy in colon cancer through the AMPK/mTOR pathway - Xiong Ni; Fu-Sheng Shang; Ting-Feng Wang; De-Jun Wu; Da-Gui Chen; Biao Zhuang (Tissue and Cell, 2023)

Novel electrochemiluminescence luminophore based on flower-like binuclear coordination polymer for high-sensitivity detection of tetracycline in food products - Guangrong Kuang; Cun Wang; Li Song; Gui Zhang; Yuqin Yang; Yingzi Fu (Food Chemistry, 2023)

Analysis of Dynamic Response and Ultimate Strength for Box Girder under Bending Moment - Gui-Jie Shi; De-Yu Wang; Fu-Hua Wang; Shi-Jian Cai (Journal of Marine Science and Engineering, 2023)
The box girder can be seen as a kind of simplified ship structure that can withstand a vertical bending moment. Dynamic loads play an important role in structural safety analysis, such as ship bow slamming during harsh sea conditions. In this paper, the dynamic elastic–plastic response and ultimate strength of a box girder under a bending moment are analyzed. A box girder with the same cross-section scantlings and span length as the Nishihara experiment is selected as the analysis object. Based on the model experiment results, the non-linear FE analysis method is validated to capture the ultimate strength of a box girder under bending moment. Then, six box girders were designed to study the critical influence factors on the dynamic ultimate moment, including the model length, plate thickness, mass density and load excitation period. On the basis of structural dynamic response, an evaluation criterion of dynamic limit state for the box girder under a bending moment is proposed in this paper. Compared with the static ultimate moment, the change in the dynamic ultimate moment is discussed in detail to obtain the general principal method for dynamic strength analysis. The conclusions in this paper can provide guidance for dynamic ultimate strength evaluation.

Ecological value of mariculture shellfish resources in China: Assessment and management - Chun-Yu Lin; Gui-Lin Dai; Yang Liu; Meng-Qi Zhang; Ying Liu; Wen Jiang; Xiu-Mei Fu; Han-Xue Chen (Marine Policy, 2023)

Modelling and analysis of unsafe acts in coal mine gas explosion accidents based on network theory - Wang Yuxin; Fu Gui; Lyu Qian; Li Xiao; Chen Yiran; Wu Yali; Xie Xuecai (Process Safety and Environmental Protection, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Hypoxia alters glucose and lipid metabolisms in golden pompano (Trachinotus blochii) - Tian Jiang; Jun Long Sun; Yue Gu; Fu Cheng Yao; Ye Song Liang; Yi Fan Liu; Kai Xi Zhang; Fei Biao Song; Li Zhou; Zhong Wei Wang; Jian Fang Gui; Jian Luo (Aquaculture, 2023)

Within-species plant phylogeny drives ectomycorrhizal fungal community composition in tree roots along a timberline - Teng Yang; Luyao Song; Han-Yang Lin; Ke Dong; Xiao Fu; Gui-Feng Gao; Jonathan M. Adams; Haiyan Chu (Soil Biology and Biochemistry, 2023)

Fine chemical speciation and environmental impact capacity of trace elements with different enrichment levels in coal - Yuan Liu; Yong Wei; Guijian Liu; Biao Fu; Bingyu Chen; Jiamei Zhang; Lin Gui; Huihui Zhou; Muyuan Lu (Science of The Total Environment, 2023)

Gold extraction using alternatives to cyanide: Ultrasonic reinforcement and its leaching kinetics - Qihao Gui; Likang Fu; Yuting Hu; Haokai Di; Ming Liang; Shixing Wang; Libo Zhang (Minerals Engineering, 2023)

Petrogenesis of Early Mesozoic volcanic rocks in southeastern NE China: Geochemical and Sr–Nd–Pb–O isotopic evidences - Jing-Yang Wei; Fu-Ping Pei; Wen-Liang Xu; Jing-Gui Sun; Hao Zhou; Tian-Jiao Sang (Lithos, 2023)

Shaking table test and numerical analysis of single-layer reticulated domes with or without three-dimensional isolation bearing - Gui-Bo Nie; Dong-fang Li; Xu-dong Zhi; Fu-yang Wang; Chen-xiao Zhang (Bulletin of Earthquake Engineering, 2022)

Chronology, geochemical characteristics, and tectonic implications of a Triassic complex in the Rongma Area, Southern Qiangtang, Tibet - Zheng-Zhe Fan; Quan Wang; Xian Chen; Gen-Hou Wang; Yue Fu; Gui-Juan Guo (International Journal of Earth Sciences, 2022)

Synthesis, antifungal activity and 3D-QSAR study of novel acyl thiourea compounds containing gem-dimethylcyclopropane ring - Mei Huang; Min Huang; Xiu Wang; Wen-Gui Duan; Gui-Shan Lin; Fu-Hou Lei (Molecular Diversity, 2022)

Genomic polymorphisms at the crhr2 locus improve feed conversion efficiency through alleviation of hypothalamus-pituitary-interrenal axis activity in gibel carp (Carassius gibelio) - Chuang Shi; Qiyong Lou; Beide Fu; Junyan Jin; Jianfei Huang; Yao Lu; Xia Jin; Jiangyan He; Gang Zhai; Shouqi Xie; Jingou Tong; Jianfang Gui; et al. (Science China Life Sciences, 2022)

Nitrogen and α-Ketoglutaric Acid Application Modulate Grain Yield, Aroma, Nutrient Uptake and Physiological Attributes in Fragrant Rice - Xiaomeng Fu; Runfei Gui; Wu Li; Zifeng Gao; Umair Ashraf; Jiangtao Tan; Qiuyi Ye; Jiale Chen; Huijia Xie; Zhaowen Mo (Journal of Plant Growth Regulation, 2021)

Neuroprotective carbazole alkaloids from the stems and leaves of Clausena lenis - Gui Yan; Yu-Jie Li; Ying-Ying Zhao; Jia-Ming Guo; Wen-Hao Zhang; Ming-Ming Zhang; Yan-Hui Fu; Yan-Ping Liu (Natural Product Research, 2021)

Genetic diversity and population structure of Tibetan sheep breeds determined by whole genome resequencing - Lei-Lei Li; Shi-Ke Ma; Wei Peng; You-Gui Fang; Hai-Rui Duo; Hong-Yun Fu; Gong-Xue Jia (Tropical Animal Health and Production, 2021)

Landslides triggered by the 6 September 2018 Mw 6.6 Hokkaido, Japan: an updated inventory and retrospective hazard assessment - Yulong Cui; Pengpeng Bao; Chong Xu; Siyuan Ma; Jun Zheng; Gui Fu (Earth Science Informatics, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Bisabolane sesquiterpenes from Clausena sanki with their potential anti-inflammatory activities - Shi Hu; Yan-Lei Ma; Jia-Ming Guo; Qing Wen; Gui Yan; Shuo Yang; Yan-Hui Fu; Yan-Ping Liu (Natural Product Research, 2020)

A big landslide on the Jinsha River, Tibet, China: geometric characteristics, causes, and future stability - Yulong Cui; Pengpeng Bao; Chong Xu; Gui Fu; Qisong Jiao; Yi Luo; Lingling Shen; Xiwei Xu; Fenglin Liu; Yuejun Lyu; Xiuhong Hu; Tao Li; et al. (Natural Hazards, 2020)

3D inversion of audio-magnetotelluric data for mineral exploration: A case study of Layikeleke buried porphyry copper deposit, Xinjiang, China - Fu Guang-Ming; Yan Jia-Yong; Chen Hui; Meng Gui-Xiang; Yu Hui; Luo Fan; Luo Lei; Tao Xin (Applied Geophysics, 2020)

Sulfide ore prospecting in carbon-containing stratum using comprehensive time-domain induced polarization and controlled-source audio-frequency magnetotellurics - Ren-Bin Sun; Li-Xia Chu; Gui-Bin Zhang; Qiu-Ming Cheng; Yun-Chuan Xiang; Bin Hu; Chang-Rong Zhang; Jian-Fu Li; Yi-Jun Zhao (Applied Geophysics, 2020)

Bioactive Eudesmane sesquiterpenes from Artabotrys hongkongensis Hance - Qing Wen; Yan-Ping Liu; Gui Yan; Shuo Yang; Shi Hu; Jing Hua; Wen-Qing Yin; Guang-Ying Chen; Yan-Hui Fu (Natural Product Research, 2020)

Influence of Aphis gossypii feeding on defense strategy of native and introduced populations of Ageratina adenophora - Ying Lin; Shu-Qi He; Zhi-Hui Lu; Yu-Lin Gao; Yan-Ru Duan; Zheng-Yue Li; Bin Chen; Fu-Rong Gui (Arthropod-Plant Interactions, 2020)

Toonapolyynes A–D, new polyynes from Toona ciliata - Rong Wang; Fu-Qiang Ni; Jun Sang; Yao Zhang; Jia-Luo Huang; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2020)

Small-scale catastrophic landslides in loess areas of China: an example of the March 15, 2019, Zaoling landslide in Shanxi Province - Yulong Cui; Chong Xu; Shiyang Xu; Shaofeng Chai; Gui Fu; Pengpeng Bao (Landslides, 2020)

Carbazole alkaloids from Clausena emarginata with their potential antiproliferative activities - Yan-Hui Fu; Yan-Lei Ma; Gui Yan; Qing Wen; Shi Hu; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Ping Liu (Natural Product Research, 2019)

An anthropogenic landslide dammed the Songmai River, a tributary of the Jinsha River in Southwestern China - Chong Xu; Yulong Cui; Xiwei Xu; Pengpeng Bao; Gui Fu; Wenliang Jiang (Natural Hazards, 2019)

Phylogeography and population genetic structure of flowering cherry species Cerasus dielsiana in subtropical China - Hong Zhu; Xian-GUI Yi; Yong-Fu Li; Shu-Xia Zhu; Meng Li; Yi-Fan Duan; Xian-Rong Wang (Systematics and Biodiversity, 2019)

Neurotrophin Receptor p75 mRNA Level in Peripheral Blood Cells of Patients with Alzheimer’s Disease - Yali Xu; Wei-Wei Li; Jun Wang; Chi Zhu; Ying-Ying Shen; An-Yu Shi; Gui-Hua Zeng; Zhi-Qiang Xu; Xin-Fu Zhou; Yan-Jiang Wang (Neurotoxicity Research, 2019)

Successful Treatment of Eczema-Like Mucormycosis in a Child by Combination of Intravenous Drip and Percutaneous Injection Amphotericin B - Mei-hua Fu; Jia Liu; Guan-zhao Liang; Cheng-rang Li; Xiao-mei Zhu; Le Wang; Hao Chen; Wen-long Hu; Gui-xia Lv; Wei-da Liu (Mycopathologia, 2019)

Identification of Gangesia oligonchis Roitman & Freze, 1964 (Cestoda: Onchoproteocephalidea) from Tachysurus fulvidraco Richardson in central China: implications for the validity of Gangesia pseudobagrae Chen, 1962 - Pei P. Fu; Wen X. Li; Hong Zou; Dong Zhang; Shan G. Wu; Ming Li; Gui T. Wang; Bing W. Xi (Systematic Parasitology, 2019)

Determination of dietary nitrite in patients with esophageal pre-cancerous lesion and normal people: a duplicate diet study - Ting Zhang; Da Pan; Ming Su; Ling-Meng Fu; Cai-Yun Miao; Qing-Yang Yan; Jing Wang; Li-Gang Yang; Shao-Kang Wang; Gui-Ju Sun (Food Additives & Contaminants: Part A, 2018)

Automatic 40Ar/39Ar Dating Techniques Using Multicollector ARGUS VI Noble Gas Mass Spectrometer with Self-Made Peripheral Apparatus - Xiu-Juan Bai; Hua-Ning Qiu; Wen-Gui Liu; Lian-Fu Mei (Journal of Earth Science, 2018)

Potential gray matter unpruned in adolescents and young adults dependent on dextromethorphan-containing cough syrups: evidence from cortical and subcortical study - Ying-wei Qiu; Xiao-fei Lv; Gui-hua Jiang; Huan-Huan Su; Xiao-fen Ma; Jun-zhang Tian; Fu-zhen Zhuo (Brain Imaging and Behavior, 2017)

Development of Albumin Coupled, Cholesterol Stabilized, Lipid Nanoemulsion of Methotrexate, and TNF-α Inhibitor for Improved In Vivo Efficacy Against Rheumatoid Arthritis - Xiao-yan Li; Hui Li; Yan Zhang; Shan Gao; Chun-ping Dong; Gui-fu Wu (AAPS PharmSciTech, 2017)

Deletion of mammalian sterile 20-like kinase 1 attenuates neuronal loss and improves locomotor function in a mouse model of spinal cord trauma - Pan-feng Wang; Da-yuan Xu; Yuntong Zhang; Xiao-bin Liu; Yan Xia; Pan-yu Zhou; Qing-ge Fu; Shuo-gui Xu (Molecular and Cellular Biochemistry, 2017)

Characterization and speciation of mercury in mosses and lichens from the high-altitude Tibetan Plateau - Jun-juan Shao; Cheng-bin Liu; Qing-hua Zhang; Jian-jie Fu; Rui-qiang Yang; Jian-bo Shi; Yong Cai; Gui-bin Jiang (Environmental Geochemistry and Health, 2017)

Toxicity and accumulation of zinc pyrithione in the liver and kidneys of Carassius auratus gibelio: association with P-glycoprotein expression - Tao Ren; Gui-Hong Fu; Teng-Fei Liu; Kun Hu; Hao-Ran Li; Wen-Hong Fang; Xian-Le Yang (Fish Physiology and Biochemistry, 2017)

Seroprevalence and risk factors of bovine viral diarrhoea virus (BVDV) infection in yaks (Bos grunniens) in northwest China - Jian-Gang Ma; Wei Cong; Fu-Heng Zhang; Sheng-Yong Feng; Dong-Hui Zhou; Yi-Ming Wang; Xing-Quan Zhu; Hong Yin; Gui-Xue Hu (Tropical Animal Health and Production, 2016)

Transcriptome analysis of sika deer in China - Bo-Yin Jia; Heng-Xing Ba; Gui-Wu Wang; Ying Yang; Xue-Zhe Cui; Ying-Hua Peng; Jun-Jun Zheng; Xiu-Mei Xing; Fu-He Yang (Molecular Genetics and Genomics, 2016)

Effect of Lactobacillus Strains on Intestinal Microflora and Mucosa Immunity in Escherichia coli O157:H7-Induced Diarrhea in Mice - Xin Bian; Ting-ting Wang; Min Xu; Smith Etareri Evivie; Guang-Wen Luo; Hong-zhang Liang; Shang-fu Yu; Gui-Cheng Huo (Current Microbiology, 2016)

Sorghum and Switchgrass as Biofuel Feedstocks on Marginal Lands in Northern China - Hai Mei Fu; Fan Yu Meng; R. L. Molatudi; Bao Gui Zhang (BioEnergy Research, 2016)

Ectomycorrhizae of Tuber huidongense and T. liyuanum with Castanea mollissima and Pinus armandii - Shan-Ping Wan; Fu-Qiang Yu; Li Tang; Ran Wang; Yun Wang; Pei-Gui Liu; Xiang-Hua Wang; Yi Zheng (Mycorrhiza, 2016)

Cloning and characterization of the gene for l-amino acid oxidase in hybrid tilapia - Yubang Shen; Gui Hong Fu; Feng Liu; Gen Hua Yue (Molecular Biology Reports, 2015)

Treatment of Benign Prostatic Hyperplasia by Ultrasound-Guided Botulinum Toxin Type A Injection - Xu-Dong Ding; Huan-Xian Chen; Hong-Qiong Xiao; Wei Wang; Zhi-Gang Ding; Gui-Bin Zhang; Du-Guan Fu (Cell Biochemistry and Biophysics, 2015)

Development and evaluation of a new interferon-gamma release assay for the diagnosis of tuberculosis infection in HIV-infected individuals in China - Liang Yu; Pingzheng Mo; Zeping Wei; Ruiling Fu; Mai Yang; Binying Ji; Jian Wang; Shu Li; Amie J. Strong; Neal Touzjian; Nicholas Kushner; Xi-En Gui; et al. (Infectious Diseases, 2015)

Detection and Characterization of Avastrovirus Associated with Diarrhea Isolated from Minks in China - Na Sun; Yong Yang; Gui-Sheng Wang; Xi-Qun Shao; Shu-Qin Zhang; Feng-Xue Wang; Bin Tan; Fu-Lin Tian; Shi-Peng Cheng; Yong-Jun Wen (Food and Environmental Virology, 2014)

The Impact of Microbial Immune Enteral Nutrition on the Patients with Acute Radiation Enteritis in Bowel Function and Immune Status - Feng shao; Fu-ze Xin; Cheng-gang Yang; Dao-gui Yang; Yue-tang Mi; Jun-xiu Yu; Guo-yong Li (Cell Biochemistry and Biophysics, 2014)

Utilization of crop heterosis: a review - Donghui Fu; Meili Xiao; Alice Hayward; Ying Fu; Gui Liu; Guanjie Jiang; Haihuan Zhang (Euphytica, 2014)

Role of Angptl4 in vascular permeability and inflammation - Liang Guo; Shao-Ying Li; Fu-Yun Ji; Yun-Feng Zhao; Yu Zhong; Xue-Jun Lv; Xue-Ling Wu; Gui-Sheng Qian (Inflammation Research, 2014)

( − )-Arctigenin as a lead compound for anticancer agent - Gui-Rong Chen; Hong-Fu Li; De-Qiang Dou; Yu-Bin Xu; Hong-Shuai Jiang; Fu-Rui Li; Ting-Guo Kang (Natural Product Research, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

An integrated East China Sea–Changjiang Estuary model system with aim at resolving multi-scale regional–shelf–estuarine dynamics - Jianzhong Ge; Pingxing Ding; Changsheng Chen; Song Hu; Gui Fu; Lunyu Wu (Ocean Dynamics, 2013)

Analysis of genetic diversity of Ruthenia Medic (Medicago ruthenica (L.) Trautv.) in Inner Mongolia using ISSR and SSR markers - Hong-yan Li; Zhi-yong Li; Li-yan Cai; Wen-gui Shi; Fu-gui Mi; Feng-ling Shi (Genetic Resources and Crop Evolution, 2013)

Screening Chinese soybean genotypes for Agrobacterium-mediated genetic transformation suitability - Zhang-yue Song; Jing-luan Tian; Wei-zhe Fu; Lin Li; Ling-hong Lu; Lian Zhou; Zhi-hui Shan; Gui-xiang Tang; Hui-xia Shou (Journal of Zhejiang University-SCIENCE B, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

The UDP glucose: flavonoid-3-O-glucosyltransferase (UFGT) gene regulates anthocyanin biosynthesis in litchi (Litchi chinesis Sonn.) during fruit coloration - Zhi Chang Zhao; Gui Bing Hu; Fu Chu Hu; Hui Cong Wang; Zhuan Ying Yang; Biao Lai (Molecular Biology Reports, 2012)

Synthesis of (–)-arctigenin derivatives and their anticancer activity - Chen Gui-Rong; Cai Li-Ping; Dou De-Qiang; Kang Ting-Guo; Li Hong-Fu; Li Fu-Rui; Jiang Ning (Natural Product Research, 2012)

Molecular epidemiology of norovirus gastroenteritis in children in Jiangmen, China, 2005–2007 - Ying-chun Dai; Gui-fang Hu; Xu-fu Zhang; Can-lei Song; Wen-long Xiang; Xian-bo Wu; Le-yi Wang; Xi Jiang; Jun Nie (Archives of Virology, 2011)

PTOV1 is associated with UCH-L1 and in response to estrogen stimuli during the mouse oocyte development - Yu-Wei Yao; Yan Shi; Zhe-Fu Jia; Ya-Hong Jiang; Zheng Gu; Jian Wang; Mohamad Aljofan; Zhao-Gui Sun (Histochemistry and Cell Biology, 2011)

Distribution pattern of plant species diversity in the mountainous Region of Ili River Valley, Xinjiang - Yuanjie Xu; Yaning Chen; Weihong Li; Aihong Fu; Xiaodong Ma; Dongwei Gui; Yapeng Chen (Environmental Monitoring and Assessment, 2011)

Cumulate hornblendite enclaves in diorite–porphyrite intrusions from the Shuangyashan, Northeast China, and implications for the transition from lower crust to upper mantle in subduction setting - Lei Zhang; Bao-Fu Han; Chun-Jing Wei; Gui-Ming Shu (International Journal of Earth Sciences, 2011)

IL-6/STAT3/TFF3 signaling regulates human biliary epithelial cell migration and wound healing in vitro - Gui-xing Jiang; Xiang-yu Zhong; Yun-fu Cui; Wei Liu; Sheng Tai; Zhi-dong Wang; Yu-guang Shi; Shi-yong Zhao; Chun-long Li (Molecular Biology Reports, 2010)

Nicotine dependence and serum BDNF levels in male patients with schizophrenia - Xiang Yang Zhang; Mei Hong Xiu; Da Chun Chen; Fu De Yang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2010)

Occurrence and distribution of polycyclic aromatic carbons in sludges from wastewater treatment plants in Guangdong, China - Xiangying Zeng; Zheng Lin; Hongyan Gui; Wenlan Shao; Guoying Sheng; Jiamo Fu; Zhiqiang Yu (Environmental Monitoring and Assessment, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

Investigations on boron levels in drinking water sources in China - Ren-ji Xu; Xiao-ru Xing; Qun-fang Zhou; Gui-bin Jiang; Fu-sheng Wei (Environmental Monitoring and Assessment, 2010)

The metabolic responses and acid–base status after feeding, exhaustive exercise, and both feeding and exhaustive exercise in Chinese catfish (Silurus asotus Linnaeus) - Ke-Gui Li; Zhen-Dong Cao; Jiang-Lan Peng; Shi-Jian Fu (Journal of Comparative Physiology B, 2010)

Protective effect of selaginellin on glutamate-induced cytotoxicity and apoptosis in differentiated PC12 cells - Chen-Jing Wang; Chang-Ping Hu; Kang-Ping Xu; Qiong Yuan; Fu-Shuang Li; Hui Zou; Gui-Shan Tan; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Isolation and characterization of polymorphic microsatellite markers in the yellow catfish, Pelteobagrus fulvidraco - Guang-Fu Hu; Hong-Wei Liang; Zhong Li; Chang-Zhong Wang; Qin-Chao Wu; Xiang-Jiang Liu; Xiang-Zhong Luo; Gui-Wei Zou (Conservation Genetics Resources, 2009)

Mycorrhizal synthesis of Tuber indicum with two indigenous hosts, Castanea mollissima and Pinus armandii - Li-Ying Geng; Xiang-Hua Wang; Fu-Qiang Yu; Xiao-Juan Deng; Xiao-Fei Tian; Xiao-Fei Shi; Xue-Dan Xie; Pei-Gui Liu; Yu-Ying Shen (Mycorrhiza, 2009)

Characterization and SNP Identification of Part of the Goat Melanophilin Gene - Fu-Jun Feng; Xiang-Long Li; Rong-Yan Zhou; Gui-Ru Zheng; Lan-Hui Li; Dong-Feng Li (Biochemical Genetics, 2009)

Studies on the Toxicological Effects of PFOA and PFOS on Rats Using Histological Observation and Chemical Analysis - Lin Cui; Qun-fang Zhou; Chun-yang Liao; Jian-jie Fu; Gui-bin Jiang (Archives of Environmental Contamination and Toxicology, 2009)

Variations in arsenic methylation capacity and oxidative DNA lesions over a 2-year period in a high arsenic-exposed population - Yuan-yuan Xu; Yi Wang; Xin Li; Miao He; Peng Xue; Jing-qi Fu; Hui-hui Wang; Gui-fan Sun (International Archives of Occupational and Environmental Health, 2009)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Population genetics of Ageratina adenophora using inter-simple sequence repeat (ISSR) molecular markers in China - Fu-Rong Gui; Fang-Hao Wan; Jian-Ying Guo (Plant Biosystems, 2008)

Reduced expression of GSTM2 and increased oxidative stress in spontaneously hypertensive rat - Si-Gui Zhou; Ping Wang; Rong-Biao Pi; Jie Gao; Jia-Jia Fu; Jian Fang; Jia Qin; Hui-Jie Zhang; Rui-Fang Li; Shao-Rui Chen; Fu-Tian Tang; Pei-Qing Liu (Molecular and Cellular Biochemistry, 2008)

Genetic analysis for brix weight per stool and its component traits in sugarcane (Saccharum officinarum) - Gui-fu Liu; Hong-kai Zhou; Han Hu; Zi-hong Zhu; Yousaf Hayat; Hai-ming Xu; Jian Yang (Journal of Zhejiang University-SCIENCE B, 2007)

Expression of a grape calcium-dependent protein kinase ACPK1 in Arabidopsis thaliana promotes plant growth and confers abscisic acid-hypersensitivity in germination, postgermination growth, and stomatal movement - Xiang-Chun Yu; Sai-Yong Zhu; Gui-Feng Gao; Xiao-Jing Wang; Rui Zhao; Ke-Qin Zou; Xiao-Fang Wang; Xiao-Yan Zhang; Fu-Qing Wu; Chang-Cao Peng; Da-Peng Zhang (Plant Molecular Biology, 2007)

Effect of α-synuclein on the promoter activity of tyrosine hydroxylase gene - Nan Gao; Yao-Hua Li; Xin Li; Shun Yu; Gui-Lian Fu; Biao Chen (Neuroscience Bulletin, 2007)

Removal of dibutyl phthalate by a staged, vertical-flow constructed wetland - Wen Yu Zhao; Zhen Bin Wu; Qiao Hong Zhou; Shui Ping Cheng; Gui Ping Fu; Feng He (Wetlands, 2004)

Study on the framework system of digital agriculture - Yong Liang; Xiu-shan Lu; De-gui Zhang; Fu Liang; Zhi-bo Ren (Chinese Geographical Science, 2003)

The effect of lanthanide chloride on abscisic acid and electron-transport activity of some crops - Fu Li Zeng; Ming Feng Zhang; Shao Min Zhou; Ji Gui Wu; Ru Wen Deng (Biological Trace Element Research, 1999)